ANALISIS PENGARUH TINGKAT PENDIDIKAN TERHADAP KOMPETENSI PEKERJA KONSTRUKSI BANGUNAN GEDUNG DI PROVINSI GORONTALO - Amala, Ikdal; Utiarahman, Arfan; Achmad, Fadly (Composite Journal, 2024)
Most of the construction workers in Indonesia are only having experience-based knowledge. They are skilled but are only elementary school graduates. Only a small proportion are able to reach the high school level. This is a fundamental problem for construction workers in Indonesia because many of the construction workers lack in engineering knowledge. This is a descriptive qualitative study. The findings indicate that: 1) Field identification, referring to the 2016 and 2013 SKKNI, reveals that both respondents are still lacking in the application of Occupational Health and Safety (K3). 2) The utility factor values ​​of the two respondents are both above 50%, where the utility factor of the blacksmith is 63.96% with a work productivity ratio of 18.39 kg/hour, while the of carbon steel worker 63.42% with productivity work of 2.73 m2/hour. 3) Both respondents occupy the lower level in the IQF, where blacksmith is categorized at level 1 and carbon steel workers is categorized at level 2. 4) The education level of construction workers does not affect their competence. Most of the knowledge related to the guild profession is obtained from work experience factors.